2004
DOI: 10.1179/003258904225020738
|View full text |Cite
|
Sign up to set email alerts
|

New technological approach to fabrication of high density PM parts by cold pressing sintering

Abstract: A new technological approach to the fabrication of high density powder metallurgy (PM) parts via single pressing sintering, allowing cold compaction to be performed without admixed lubricants, has been studied. The influence of in pore gas on the compacts' green density and their sintered properties were evaluated. A mathematical expression relating in pore gas pressure in the compacts to the green density was developed. The expression showed that in order to reduce the negative influence of gases trapped in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Mamedov and Mamedov [5] presented a new fabrication method for the manufacturing of high density powder metallurgy parts using single pressing cold sintering technique. Using SEM images they estimated the compact green density of samples and explored the influence of the processing conditions on the density.…”
Section: Experimental Measurement Of Density Distributionmentioning
confidence: 99%
“…Mamedov and Mamedov [5] presented a new fabrication method for the manufacturing of high density powder metallurgy parts using single pressing cold sintering technique. Using SEM images they estimated the compact green density of samples and explored the influence of the processing conditions on the density.…”
Section: Experimental Measurement Of Density Distributionmentioning
confidence: 99%
“…Goodness of fit was evaluated from 'R-Square' and Adj. 'R-Square' in order to check the reliability and precision of the model [7,8]. The ANOVA table, by selecting the manual procedure for the response at rolled condition, is given as Table 3.…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 99%
“…It was found that yielding of sintered materials is sensitive to hydrostatic stresses component imposed, as yield surface closes on the hydrostatic stress axis. Mamedov and Mamedov [9] presented a new fabrication method for the manufacturing of increased density powder metallurgy components using single press cold sintering technique. Using SEM images they estimated the compact green density of samples and explored the influence of the processing conditions on the density.…”
Section: Introductionmentioning
confidence: 99%